Carbetosine, a Long-acting Oxytocin Agonist, as a Uterotonic in the Prevention of the Occurrence of Postpartum Bleeding - Izaak, Revynca Petronella (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To evaluate the comparative effect of carbetocin vs. other uterotonic agents in the prevention of the occurrence of postpartum bleeding. Methods: Medical search engines like Pubmed, Google Scholar, and Cochrane are used for literature searches. The year period covered by the literature is 2013–2023. “Carbetocin” or “long-acting oxytocin” and “uterotonic” are the essential words, together with “post-partum hemorrhage” or “post-partum bleeding.” Data analysis was performed using the RevMan 5.4 application. Results: This study involved 12 clinical trials with a total sample of 32,312 people. Based on forest plot analysis, it was found that patients receiving carbetocin therapy had a risk of developing postpartum bleeding of 0.42 times compared to those receiving other uterotonic agents (misoprostol and oxytocin) (OR: 0.42; 95% CI: 0.26-0.68; p<0.0004; with heterogeneity p<0.00001, I2 85%) Conclusion: With its effectiveness and efficacy, carbetocin can be considered one modality that can prevent postpartum hemorrhage. In addition, it can benefit women at risk of having a major obstetric hemorrhage. Keywords: carbetocin, uterotonic, meta-analysis, clinical trial